Technology management and american culture implications for business process redesign - Baba, Marietta
Marietta L. Baba, Donald R. Falkenburg and David H. Hill explore the interaction between culture and a corporation's efforts to redesign its business processes.
Seeing beyond corporate cultural boundaries is a necessary first step toward effective process integration and corporate transformation. But to ignore national culture is to invite failure.
Culture creates barriers to business process reengineering. Three distinctive levels of culture must be recognized in process redesign-national, corporate and work group culture. American national culture has the most profound influence. Individualism and autonomy are key features of American culture that work against the logic of process integration and commonization by rewarding individuals for pursuing their own self-interests. This tendency also generates a lack of trust, which in turn creates barriers to sharing electronic data. Reengineering difficulties are exacerbated by an American fascination with technological solutions, and a view of new technology as a "silver bullet" that yields benefits automatically. Often, process redesign cannot be implemented without culture change. Culture can be influenced by exposing internal groups to external pressures, ensuring employee participation in reengineering, recognizing that training alone does not achieve culture change, redefining group boundaries, managing anti-champions, building trust, and leveraging the strengths of national and corporate culture.
Keywords: Technology management--America.; Business process redesign